PENGEMBANGAN MEDIA PEMBELAJARAN TRIGONOMETRI PENDUKUNG PEMBELAJARAN TERDIFERENSIASI KELAS X MADRASAH ALIYAH NEGERI TANJUNGPINANG - Nadila Witriani Nadila Witriani; Mariyanti Elvi; Nur Asma Riani Siregar (Jurnal Karya Pendidikan Matematika, 2024)
This research aims to develop Trigonometry learning media to support differentiated learning for class X that is valid and practical. This research method is Research and Development involving 2 material expert validators and 2 media expert validators. The subjects of this research were 65 students in class X Madrasah Aliyah Negeri Tanjungpinang. The data collected are interviews, observations and questionnaires which include validation by media experts and material experts, as well as student and teacher response questionnaires. The results of the research show that the validity assessment by material experts on trigonometry learning media supporting differentiated learning is at 90.00% (Very Valid), the validity assessment by media experts is 91.00% (Very Valid), the results of assessing the practicality of educators' responses are at 95.00% (Very Practical) and the results of assessing the practicality of student responses were 90.15% (Very Practical). So it can be stated that trigonometry learning media is suitable for use as a support for differentiated learning for class X Madrasah Aliyah Negeri Tanjungpinang